2017
DOI: 10.1016/j.yjmcc.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic induced SR Ca 2+ leak is mediated by an Epac-NOS pathway

Abstract: Cardiac β-adrenergic receptors (β-AR) and Ca2+-Calmodulin dependent protein kinase (CaMKII) regulate both physiological and pathophysiological Ca2+ signaling. Elevated diastolic Ca2+ leak from the sarcoplasmic reticulum (SR) contributes to contractile dysfunction in heart failure and to arrhythmogenesis. β-AR activation is known to increase SR Ca2+ leak via CaMKII-dependent phosphorylation of the ryanodine receptor. Two independent and reportedly parallel pathways have been implicated in this β-AR-CaMKII casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 43 publications
1
51
0
Order By: Relevance
“…Recent studies indicate that β-adrenergic signaling promotes NO production in cardiomyocytes (29,(56)(57)(58). In addition to the canonical pathway of NO-induced protein kinase G activation, NO also induces direct posttranslational modification of thiol groups in specific cysteine residues on various proteins via S-nitrosylation (59).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that β-adrenergic signaling promotes NO production in cardiomyocytes (29,(56)(57)(58). In addition to the canonical pathway of NO-induced protein kinase G activation, NO also induces direct posttranslational modification of thiol groups in specific cysteine residues on various proteins via S-nitrosylation (59).…”
Section: Discussionmentioning
confidence: 99%
“…The β-AR signaling pathway, which is classically activated by catecholamines, is one of the well-known pathways in the induction of cardiac hypertrophy [ 12 , 13 ]. The activation of β-AR regulates cardiac excitation–contraction and leads to the increase in heart rate and cardiomyocyte contractility [ 21–23 ]. The hyperactivation of β-AR results in cardiac hypertrophy, fibrosis, senescence, inflammation, and cardiomyocyte apoptosis and necrosis [ 24–29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A second pathway, independent of cAMP, involves PI3K and Akt as upstream activators of nNOS inducing CaMKII activation via nitrosylation ( Curran et al, 2014 ). A recent study suggested that the Epac and nNOS pathway are interdependent and function largely in series ( Pereira et al, 2017 ).…”
Section: β-Adrenergic Signaling and Afterdepolarizationsmentioning
confidence: 99%